Current management of skin conditions in Kenya: exploring teledermatology preferences and perspectives among providers - Jennifer M. Fernandez, MD, RD; Hashim Kaderbhai, MMed; Jennifer L. Adams, MD; Mary B. Adam, MD, MA, PhD; Rodney D. Adam, MD (International Journal of Women's Dermatology)
Background:. Teledermatology programs may help expand access to care for skin conditions in areas that are underserved by dermatologists such as sub-Saharan Africa, but their success requires input from participating providers. Objective:. This study assesses teledermatology preferences among healthcare providers in Kenya. Methods:. An anonymous cross-sectional survey of nondermatology providers was conducted in Kenya from January to March 2024 at Aga Khan University Hospital-Nairobi and Kijabe Hospital. Results:. Among the 38 providers, 81.6% were physicians. Patient population was primarily Fitzpatrick skin types V and VI. Almost all (97.4%) regularly encountered patients with skin disorders, yet only 5.3% felt comfortable diagnosing and treating 80 to 100% of these disorders independently. Providers anticipated referring cases of rashes (76.3%), unclear diagnoses (63.2%), and infectious diseases (50%), among others, for teledermatology consultation. Only 10.5% reported utilizing teledermatology, although the majority believed it would be useful (91.9%) and improve patient care (89.5%). Preferred response time was <24 hours (81.6%). Most favored submitting cases via personal cell phones (86.8%), with 87.9% preferring submission through WhatsApp. Limitations:. Participants owned smartphones. The survey was distributed via WhatsApp. Conclusion:. Nearly all providers in Kenya see patients with skin conditions, but few utilize teledermatology services. Teledermatology could be extremely beneficial for patients and providers seeking dermatologic expertise.